Agricultural residues incorporated to commercial substrates in the production of cabbage seedlings (Revista de Ciências Agroveterinárias, 2018)
In the production of quality vegetables, the formation of seedlings is one of the most important phases for the crop cycle, directly influencing the final performance of the plant, both from a nutritional and productive point of view. One of the decisive factors to obtain seedlings with quality and consequent increase in productivity is the type of substrate used. The objective of this research was to evaluate the effect of increasing proportions of residues from the drying of coffee beans (chaff) on alternative substrates constituted by coconut fiber, eggshell and commercial substrate, in the growth variables of cabbage seedlings. The experiment was conducted under a completely randomized design, with five treatments and ten replicates, with the following treatments: T0: commercial substrate (control); T1: 10% chaff (CH) + 15% coconut fiber (CF) + 5% eggshell (ES) + 70% commercial substrate (CS); T2: 20% CH + 15% CF + 5% ES + 60% CS; T3: 30% CH + 15% CF + 5% ES + 50% CS; T4: 40% CH + 15% CF + 5% ES + 40% CS. The evaluated variables were substrate electrical conductivity, collection diameter, number of leaves, height of plants and dry matter of shoot, root, and total plant. The highest values obtained from the variables analyzed were obtained in the treatment 4, in which 40% of woodwool + 15% coconut fiber + 5% eggshell + 40% commercial substrate were used.
Keywords: Brassica oleracea; chaff; coconut fiber; eggshell